FACTORS FORMING THE HEALTH OF MEDICAL FACULTY STUDENTS - Abdurakhmanov K.H.; Safarova Asila (Journals Park Publishing, 2024)
The new millennium in human history began under environmental conditions that underwent significant changes back in the twentieth century. In the thousand-year history of mankind, the previous century was perhaps one of the most turbulent and eventful. In no other century have human activities and living conditions changed as rapidly as in the twentieth century, and the change in people's living conditions was directly related to the influence of scientific and technological progress.